2017
DOI: 10.1038/s41598-017-10869-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional prediction of long non-coding RNAs in ovarian cancer-associated fibroblasts indicate a potential role in metastasis

Abstract: Cancer-associated fibroblasts (CAFs) contribute to the poor prognosis of ovarian cancer. Unlike in tumour cells, DNA mutations are rare in CAFs, raising the likelihood of other mechanisms that regulate gene expression such as long non-coding RNAs (lncRNAs). We aimed to identify lncRNAs that contribute to the tumour-promoting phenotype of CAFs. RNA expression from 67 ovarian CAF samples and 10 normal ovarian fibroblast (NOF) samples were analysed to identify differentially expressed lncRNAs and a functional net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 75 publications
(59 reference statements)
0
38
0
Order By: Relevance
“…Numerous studies have confirmed the strong correlations between lncRNAs and various human diseases, including cancers, Alzheimer's disease, and cardiovascular diseases . Some lncRNAs are reported to participate and play critical roles in tumorigenesis, including the generation, growth, and metastasis of cancers from several types of tissue origins . For instance, the expression of the lncRNA XIST is highly upregulated in bladder cancer and is involved with the development of bladder tumorigenesis, whereas SNHG5, another tumor‐related lncRNA, is overexpressed in chronic myeloid leukemia…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have confirmed the strong correlations between lncRNAs and various human diseases, including cancers, Alzheimer's disease, and cardiovascular diseases . Some lncRNAs are reported to participate and play critical roles in tumorigenesis, including the generation, growth, and metastasis of cancers from several types of tissue origins . For instance, the expression of the lncRNA XIST is highly upregulated in bladder cancer and is involved with the development of bladder tumorigenesis, whereas SNHG5, another tumor‐related lncRNA, is overexpressed in chronic myeloid leukemia…”
Section: Introductionmentioning
confidence: 99%
“…21 Some lncRNAs are reported to participate and play critical roles in tumorigenesis, including the generation, growth, and metastasis of cancers from several types of tissue origins. [22][23][24] For instance, the expression of the lncRNA XIST is highly upregulated in bladder cancer and is involved with the development of bladder tumorigenesis, 25 whereas SNHG5, another tumor-related lncRNA, is overexpressed in chronic myeloid leukemia. 26 Our study has confirmed that the metastasis associated lung adenocarcinoma transcript 1 (MALAT1), an 8.1-kb lncRNA transcribed from the nuclear-enriched transcript 2 (NEAT2), is significantly overexpressed in colorectal cancer (CRC).…”
mentioning
confidence: 99%
“…Long non‐coding RNA (lncRNA) is known as a type of noncoding RNA with over 200 nucleotides in length and non‐protein coding ability . It has been certified that abnormal expression of lncRNAs plays a vital role in the progression of various cancers such as ovarian cancer, colon cancer and gastric cancer . Therefore, studying lncRNAs may be of great value in exploring the occurrence and development of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…45 These secreted ECM proteins, in turn, trigger a plethora of signaling pathways as PI3K-AKT as well as NFkB that promote OvCa spread, recurrence and chemoresistance. 45,59,60 In addition, increased number of CAFs was associated with advanced OvCa stage, higher frequency of metastases, and lymphatic and microvessel density. 48 The findings that the molecular cross-talk between cancer cells and CAFs in the OvCa TME is regulated by TGFβ/TGFβRs/SMAD pathway in CAFs and triggers multiple oncogenic pathways in OvCa cells warranted the initiation of clinical trials targeting TGFβ/TGFβRs as well as PI3K inhibitors in combination with standard of care therapy (summarized in Table 1).…”
Section: Cancer-associated Fibroblasts (Cafs) the Origin Ofmentioning
confidence: 97%
“…Other secreted ECM proteins upregulated and secreted by CAFs include periostin, secreted phosphoprotein, and cartilage oligomeric matrix protein (COMP) . These secreted ECM proteins, in turn, trigger a plethora of signaling pathways as PI3K‐AKT as well as NFkB that promote OvCa spread, recurrence and chemoresistance . In addition, increased number of CAFs was associated with advanced OvCa stage, higher frequency of metastases, and lymphatic and microvessel density .…”
Section: Introductionmentioning
confidence: 99%